(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The present study was undertaken to investigate the antidiabetic effect of the bitter melon and black cumin on alloxan induced diabetes in experimental rabbits. At 2 to 3 months of age, rabbits were assigned into five groups (A, B, C, D and E) and rabbits were included each group. Group A was kept as control, Group B was treated with alloxan intramuscularly at a dose of 75mg /kg body weight, Group C was treated with bitter melon at a dose of 150gm/kg body weight orally, Group D was treated with black cumin at a dose of 250mg/kg body weight orally, Group E was treated with combined at previous dose. After acclimatization, diabetes was induced in four groups of rabbits (B, C, D and E) by administering alloxan injection. There was significant (p<0.05) decreased in blood glucose level in all treated group C, D, E compared to the B group and lowest glucose was recorded in E group when treated with combined medicinal herbs and body weight was increased in all treated group C, D, E compared to the B group and highest was recorded in D group while treated with those. % of PCV level and Hbgm/dl concentration was the highest in group E which was treated with both black cumin and bitter melon compare to the A group. ESR was highest in group B treated with alloxan and lowest in group E. The present study demonstrated that combined treatment increased body weight and decreased glucose level without affecting health of rabbits. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 24-28